Implementasi Pembelajaran PAI dan Budi Pekerti Integratif Berbasis Probing Prompting di SMP - roki; Fadriati (Jurnal Pendidikan Islam, 2023)
This study examines the implementation of integrative PAI and Character learning based on probing prompting. The problem is that the challenge of education today is to make learning fun and student-centered. From these problems research questions emerged: 1) how to plan integrative PAI and BP learning based on probing prompting, 2) how to implement integrative PAI and BP learning based on probing prompting 3) how to evaluate integrative PAI and BP learning based on probing prompting. This research is field research. Data was obtained through observation and interviews. After the data is collected, it is processed by means of data reduction, data presentation and drawing conclusions. Next, the data is narrated descriptively. The results are discussed with the theories put forward. This research found that integrative learning planning includes preparation of teaching modules; PAI learning integration; media; probing prompting technique. Implementation of learning includes opening activities, probing, responding to student answers, prompting, monitoring, teacher reinforcement. Learning evaluation covers the three domains of student learning outcomes. The results obtained were that students were enthusiastic in learning and active in answering questions with probing and prompting questions.